Functional characterization of one sex pheromone receptor (AlucOR4) in Apolygus lucorum (Meyer-Dür). (January 2020) - An, Xingkui; Khashaveh, Adel; Liu, Danfeng; Xiao, Yong; Wang, Qi; Wang, Shanning; Geng, Ting; Gu, Shaohua; Zhang, Yongjun
Graphical abstract: Highlights: We identified one candidate sex pheromone receptor, AlucOR4, from Apolygus lucorum . AlucOR 4 was highly expressed in the male antennae. AlucOR4/AlucOrco was sensitive to ( E )-2-hexenyl butyrate and hexyl butyrate. EAG responses to ( E )-2-hexenyl butyrate and hexyl butyrate were reduced after RNAi. Abstract: Traps baited with female-produced sex pheromones have been very effective in the monitoring and management of mirid bugs in numerous field trials. However, none of the target odorant receptors for sex pheromone components in Apolygus lucorum have been identified. Here, we identified one candidate sex pheromone receptor, AlucOR4, from A. lucorum . Quantitative real-time PCR (qPCR) analysis revealed that AlucOR 4 was antennae-enriched and male-biased in adult A. lucorum. Xenopus oocyte expression system assays demonstrated that AlucOR4/AlucOrco was sensitive to two major sex pheromone constituents and exhibited high sensitivity to ( E )-2-hexenyl butyrate (E2HB) and lower sensitivity to hexyl butyrate (HB). The expression level of target mRNA was significantly reduced (>80%) in ds AlucOR 4-injected bugs after five days. The electroantennogram (EAG) responses of male antennae to E2HB and HB were also reduced significantly ( 40%). Our findings suggest that AlucOR4 is essential to sex pheromone perception in A. lucorum .